Evaluación ultrasonográfica de la pared del estómago equino durante el ayuno y post ingesta líquida (Veterinary Science, 2017)
Ultrasonography allows evaluating the anatomy and functional dynamics of the equine stomach.The aim of this study was to evaluate the dynamics of the equine stomach, standardizing the window of exploration of the same one.Ten healthy horses were evaluated using ultrasound methodology.With a previous solid and liquid fasting of 7 and 5 hours respectively, there measured up the thickness of stomach wall, repeating the procedure after the ingestion of liquid.The results analyzed statistically allowed to infer that: a)there is an important association between wall thickness decrease and liquid ingestion. b)The Coefficient of Regression does not explain a causal relationship (ingest)/effect (decrease of thickness). c) The Coefficient of Determination admits linear slightly significant relationship between liquid ingestion and decrease of the thickness wall. d)There are very significant differences between the averages of the thickness of the equine stomach wall in fasting and with liquid ingestion.
Keywords: Ultrasonography; Abdomen; Stomach